Evaluating Educational Recommendation Systems: a systematic mapping - Marante, Yelco; Silva, Vinicius Alberto Alves da; Gomes Jr., Jorão; Vitor, Marluce Aparecida; Martins, André Ferreira; De Souza, Jairo Francisco (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2020)
Recommendation systems (RS) have been used in many scenarios, from entertainment to health. Inside the RS area, Educational Recommendation Systems (ERS) are becoming popular, been used for different types of recommendations such as recommending materials, exercises, and learning paths. As ERS works in a different scenario of classics RS, ERS requires specific evaluation metrics. However, the task of evaluating ERS is difficult once the educational field has its features to be analyzed. To help other researchers in this field, this work presents a systematic mapping on methods used for evaluating ERS. This study analyzed 91 papers of the last five years and provide an overview of the main methodologies, subject, metrics, and trends in the evaluation of ERS.